1976
DOI: 10.1128/iai.14.2.416-421.1976
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between Coxiella burnetii and guinea pig peritoneal macrophages

Abstract: The phagocytosis and subsequent degradation of phase I and II Coxiella burnetii by macrophages obtained from immune and nonimmune guinea pigs were compared. Phase I rickettsiae were more resistant to phagocytosis than were phase II organisms. There was no significant difference in the percentage of phagocytosis of either phase of rickettsiae by macrophages from immune or nonimmune animals. After ingestion, phase I and II organisms pretreated with normal serum multiplied and destroyed normal macrophages as well… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
25
0

Year Published

1977
1977
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 16 publications
4
25
0
Order By: Relevance
“…Preparation of rickettsial stock suspension. The third egg passage of the Henzerling strain of C. burnetii in phase I was grown in chicken embryo cells as previously described (17). The infectivity of the rickettsial suspension was estimated to be 109.5 mouse median infectious doses after administration by the intraperitoneal route.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Preparation of rickettsial stock suspension. The third egg passage of the Henzerling strain of C. burnetii in phase I was grown in chicken embryo cells as previously described (17). The infectivity of the rickettsial suspension was estimated to be 109.5 mouse median infectious doses after administration by the intraperitoneal route.…”
Section: Methodsmentioning
confidence: 99%
“…Previous in vitro studies indicated that homologous immune serum to phase I and II Coxiella burnetii not only enhanced the phagocytic uptake of rickettsiae (14)(15)(16)(17), but also potentiated their destruction within phagocytes (15)(16)(17). Although immune serum has not been shown to have a direct rickettsicidal action on C. burnetii, its passive transfer to nonimmune animals modifies the infection (1).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Macrophages are known to play a key role in the regulation of lymphocyte proliferation (33) and to mediate immunosuppression during numerous infectious diseases (18,35,44). Previous studies have shown that phase I C. burnetii WCV is readily phagocytized by macrophages and that this results in nonspecific activation of these cells (15,20). Preliminary experiments with prostaglandin synthesis inhibitors (9,32), macrophage toxins (22), cell-depletion techniques (10,13,33,38), and coculture protocols (37) suggest that the suppression and negative regulation of mouse spleen cells by phase I WCV may be mediated by T suppressor cells.…”
Section: Discussionmentioning
confidence: 99%
“…There are several reports on the CMI response against Coxiella burnetti. Heggers et al (10), Kishimoto and Burger (16), and Kishimoto and Walker (17) have described CMI events in guinea pigs, and Jerrells et al (11) have described the CMI response to C. burnetti infection in humans.…”
mentioning
confidence: 99%